Managing emotions in times of pandemic and its impact on academic performance - Hernández Abad, Genibert (2020)
To guarantee that the teaching-learning process is carried out even and with all adversities, it is necessary that before expecting excellent work, practices and participation in classes, students are taught to manage their emotions, which leads to having as study objective to discover the impact of learning to handle or manage emotions on the academic performance of students in the face of a change in educational methodology, in this case due to pandemic issues. In order to carry out this process, a survey through Google Forms was used as an instrument aimed at students between 11-18 years of age at the secondary level of a polytechnic located in Santo Domingo, Dominican Republic.